Endométriose et travail, un calvaire au féminin - Poissonnier, Gaétane (Alternatives Economiques, 2021)
Number: 2 Publisher: Alternatives économiques
Keywords: 1900-1999; 1960-1969; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; corps; cours; discipline; endométriose; europe; france; inégalités; justice reproductive; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail

Des ovocytes sous contrôle. Regards franco-suisses sur l’encadrement juridique du don et de l’autoconservation d’ovocytes - Mesnil, Marie (Nouvelles Questions Féministes, 2021)
La comparaison du droit français et suisse concernant le don et l’autoconservation d’ovocytes met en lumière des enjeux en termes de protection de l’intégrité physique, de parenté et de liberté reproductive. Au contraire de la Suisse, la France encadre le don d’ovocytes, mais n’autorise pas l’autoconservation ovocytaire. Pourtant, ces techniques ne remettent pas en cause les normes procréatives et familiales quant au bon âge de la maternité et à la conjugalité hétérosexuelle : les ovocytes - donnés ou conservés - ne peuvent être utilisés que dans le cadre légal d’une procréation médicalement assistée (PMA). L’article examine en détail le projet de loi de bioéthique qui, en France, prévoit d’ouvrir l’autoconservation ovocytaire, mais qui exclut, au sein des couples lesbiens nouvellement éligibles à la PMA, qu’une femme puisse recevoir les ovocytes de sa partenaire. L’auteure met ainsi en avant le fait que le contrôle des corps et de la sexualité des femmes perdure sous des formes renouvelées.
Number: 2
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; cours; discipline; discours dominant; droits des femmes*; europe; france; histoire et politique; justice reproductive; maternité; premier cycle; privilèges; périodes historiques; régions géographiques; santé; sciences humaines; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail; travail reproductif

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis